Effects of Polysulfide Solubility and Li Ion Transport on Performance of Li–S Batteries Using Sparingly Solvating Electrolytes. Issue 7 (5th March 2020) - Yanagi, Masato; Ueno, Kazuhide; Ando, Ayumi; Li, Shanglin; Matsumae, Yoshiharu; Liu, Jiali; Dokko, Kaoru; Watanabe, Masayoshi
Abstract : Sparingly solvating electrolytes are an emerging class of electrolytes used in Li–S batteries. In this type of electrolytes, polysulfide dissolution and shuttling can be suppressed, resulting in high Coulombic efficiency and cycle life. To optimize the electrolytes for high energy density cells, effects of polysulfide solubility and Li ion transport properties on Li–S battery performance were investigated for tetraglyme (G4)-based solvate ionic liquids [Li(G4) x ][TFSA] and a sulfolane (SL)-based concentrated electrolyte [Li(SL)2 ][TFSA], which are both diluted with a hydrofluoroether (HFE). The Li2 S8 solubility is low (1 mM in atomic S concentration) in [Li(G4)0.8 ][TFSA]−4.3HFE and [Li(SL)2 ][TFSA]−4.0HFE. Cells with [Li(SL)2 ][TFSA]−4.0HFE exhibited better rate capability despite their lower ionic conductivity. The higher transference number ( t Li + ) of [Li(SL)2 ][TFSA]−4.0HFE may predominantly contribute to the rate performance, rather than polysulfide solubility and ionic conductivity. Furthermore, [Li(SL)2 ][TFSA]−4.0HFE demonstrated an initial discharge capacity of 1130 mAh g −1 at a low electrolyte volume to sulfur weight ratio of 4, whereas a typical organic electrolyte failed to achieve such a high capacity owing to limitations of the redox mechanism mediated by dissolved polysulfides. In addition to the low solubility of polysulfides, the high t Li + is crucial for achieving high energy density Li–S batteries by reducing the electrolyte amount.